Do standards matter for export success ? - Otsuki, Tsunehiro (Policy research working paper, 2006)
"Standards and technical regulations are an increasingly prominent part of the international trade policy debate. In particular, there has been considerable discussion of whether standards and regulations affect trade costs and export prospects for developing countries. In this paper the authors examine how meeting foreign standards affects firms' export performance, reflected in export propensity and market diversification. The analysis draws on the World Bank Technical Barriers to Trade Survey database of 619 firms in 17 developing countries. The results indicate that technical regulations in industrial countries adversely affect firms' propensity to export in developing countries. In particular, testing procedures and lengthy inspection procedures reduce exports by 9 percent and 3percent, respectively. Furthermore, in the model, the difference in standards across foreign countries causes diseconomy of scale for firms and affects decisions about whether to enter export markets. The empirical analysis presented here implies that standards impede exporters' market entry, reducing the likelihood of exporting to more than three markets by 7 percent. In addition, the authors find that firms that outsource components are more challenged by compliance with multiple standards. "--World Bank web site